Effects of laparoscopic sleeve gastrectomy on concentration and composition of bile acids in an Asian population with morbid obesity. (June 2021) - Yao, Jie; Kovalik, Jean-Paul; Lai, Oi Fah; Lee, Phong Ching; Eng, Alvin Kim Hock; Chan, Weng Hoong; Lim, Eugene Kee Wee; Bee, Yong Mong; Tan, Hong Chang
Background: Bile acids (BAs) are traditionally associated with lipid absorption and phase II detoxification by forming various BA conjugates. Recently, it has been discovered that BAs also regulate glucose metabolism, and the increase in BAs in patients following bariatric surgery may contribute to the post-surgery improvement in insulin resistance (IR). However, while Roux-en-Y gastric bypass can increase BA concentrations post-surgery, this may not be the case after laparoscopic sleeve gastrectomy (LSG). We hypothesized that the profiling of BAs that include the conjugated BA species could detect post-surgery BA changes after LSG. To test our hypothesis, we performed comprehensive profiling of BAs in Asian individuals with morbid obesity at baseline, and at 6 months following LSG. Methods: Fourteen subjects scheduled for LSG were recruited. Anthropometric measurements, oral glucose tolerance test, and biochemistry tests were performed at baseline and at 6 months after LSG. BAs were profiled using liquid chromatography–mass spectrometry. Results: At 6 months, subjects lost significant weight from 117.4±5.4 to 92.1±3.8 kg and demonstrated significant improvement in IR. HOMA-IR decreased from 6.2±0.7 to 2.0±0.2 and the Matsuda index increased from 1.9±0.3 to 3.3±0.3. We did not detect any significant post-operative change in the levels of total BAs (5237.1±1219.4 vs. 3631.7±457.9, p =0.181) or non-sulfated BAs after LSG. However, sulfated BA species increased significantly after LSG. Conclusion: Our study showed that the serum concentrations of sulfated BA species in morbidly obese Asian individuals increased significantly 6 months after LSG; the increase in sulfated BAs after LSG might contribute to the post-surgery improvement of metabolic health.